If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(8x+3)-4x=3(4x+6)-23
We move all terms to the left:
2(8x+3)-4x-(3(4x+6)-23)=0
We add all the numbers together, and all the variables
-4x+2(8x+3)-(3(4x+6)-23)=0
We multiply parentheses
-4x+16x-(3(4x+6)-23)+6=0
We calculate terms in parentheses: -(3(4x+6)-23), so:We add all the numbers together, and all the variables
3(4x+6)-23
We multiply parentheses
12x+18-23
We add all the numbers together, and all the variables
12x-5
Back to the equation:
-(12x-5)
12x-(12x-5)+6=0
We get rid of parentheses
12x-12x+5+6=0
We add all the numbers together, and all the variables
11!=0
There is no solution for this equation
| 7^4=7^6-2x | | 5x-6+4=13 | | r/5+45=81 | | 2x+46=3x+1 | | x+7/14=1−3/2x | | 4/9d=-4 | | 1/2y+4=7 | | 3^3x-1=24 | | 3n-2n4=n=7n4-2 | | 10−13y=36 | | 3(3m/4-1)+m/5=42-m/4 | | 10x−13=36 | | 14n+6=202 | | x+22+2x-7=90 | | -21=-3+2a+4a | | X^2+-5x+-8=0 | | X2+-5x+8=0 | | 11a-4=18 | | 2(3+4x)-5=33 | | x^2+12-48x=0 | | 6c=126 | | 6c+c=126 | | 7=-6+6y+7 | | 6c+c=127 | | -20=-45+x | | 10x+2×+8×-7×+17(×-1)=43 | | F(x)=5/x+7 | | 80+30y=190 | | 4x+x+1=(7-3) | | 4x+x+1=7(-3) | | 1/9x^2-9=0 | | 4x(7x+2)=180 |